Some stylised facts on the euro area business cycle - Anna Maria Agresti; Benoît Mojon (European Central Bank (ECB), 2001)
This paper presents stylised facts about the business cycle of the euro area. The results suggest that the stylised facts for the euro area economy and the US are very similar. The magnitude of the fluctuations in consumption, investment, prices, inflation, interest rate, monetary aggregates relative to the fluctuations of GDP are very similar in the two monetary unions. There is also high synchronicity of the national cycles and the euro area aggregate cycle. This synchronicity is observed for the main GDP components as well as for interest rates and it is particularly high for the largest countries of the euro area and for countries of the core ERM. These results are not sensitive to a different aggregation method chosen to build euro area aggregates. However, we do find differences between the euro area and the member countries when looking at what variables are predicting inflation or GDP
Keywords: E42; E50; 330; business cycle; euro area; monetary policy